Hubungan Konsep Diri Siswa Dengan Hasil Belajar Fisika Siswa Kelas VIII SMP Negeri 9 Padangsidimpuan Hutaimbaru Tahun Ajaran 2023-2024 - Harahap, Selvina; Eni Sumanti Nasution; Sri Utami Khoilla Mora Siregar; Kasmawati (Universitas Gara Nusantara Padangsidimpuan, 2023)
This study aims to determine the relationship between self-concept and student learning outcomes in class VIII SMP Negeri 9 Padangsidimpuan Hutaimbaru Academic Year 2023-2024. The formulation of the problem obtained from this study is is there a relationship between self-concept and physics learning outcomes for Class VIII students of SMP Negeri 9 Padangsidimpuan Hutaimbaru for the 2023-2024 academic year. This research was conducted at Padangsidimpuan 9 Public Middle School with a total sample of 30 students. The instrument used was a questionnaire with a Likert scale and a test of learning outcomes through test scores at school. This type of research is quantitative research using the product moment test to test the hypothesis. Besides that, it also uses the normality test, hypothesis test and linearity test. The results of this study by conducting a correlation test obtained the relationship between self-concept and learning outcomes, this can be seen from the correlation value using the SPSS 17 application where the value is 0.048 which is smaller than the significant value of 0.05 which shows a positive relationship between self-concept and learning outcomes .